Geohazards Proceedings of IGC 2018 - Latha Gali, Madhavi; Raghuveer Rao, P.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This volume comprises select papers presented during the Indian Geotechnical Conference 2018. It discusses concepts of soil dynamics and studies related to earthquake geotechnical engineering, slope stability, and landslides. The papers presented in this volume analyze failures connected to geotechnical and geological origins to improve professional practice, codes of analysis and design. This volume will prove useful to researchers and practitioners alike. .
Seismic response of shallow strip footing with Log-spiral failure mechanism using Limit analysis -- A Comparative Study of Soil Slope stability under Seismic Loading Condition -- Investigations and Mitigation Measures of Landslide Affected Areas in Hill Roads of East Africa - Case Study on Projects of Ethiopia -- Multivariate Adaptive Regression Splines Based Reliability Analysis of Stability of Durgawati Earthen Dam -- Landslides Hazard Mapping using High-Resolution Satellite Data -- Analysis of Rainfall Induced Slope Failure Using Monte Carlo simulations: A Case Study.
Keywords: Engineering geology; Engineering$1 (BGeology.s; Foundations; Hydraulics; Geotechnical engineering; Soil science; Soil conservation; Buildings$1 (BDesign and construction.s; Building; Construction; Engineering, Architectural; Building construction; Geoengineering, Foundations, Hydraulics; Geotechnical Engineering & Applied Earth Sciences; Soil Science & Conservation; Building Construction and Design; Solid Construction